Red Stars? The Astronomical Development of Cold War Chile - Silva, Barbara; Riquelme, Alfredo (Revista de Historia Social y de las Mentalidades, 2024)
This paper analyses the Soviet Union’s scientific presence in Chile during the 1960s, specifically in the field of astronomy, within the broader context of the global Cold War. By examining this case, the paper highlights a significant scientific development connected to international dynamics, observed from a Global South perspective. The study draws on Chilean and US sources and reports to trace the flow of information, revealing a more complex structure of Cold War interactions than the traditional East-West dichotomy suggests. This approach also underscores the complexities of international relations through the lens of science.